Prevalence of sub-clinical mastitis in Uruguay - Ahlner, Sara (SLU/Dept. of Microbiology, 2003)
Uruguay is a major milk producer and exporter of dairy products in South America with 1,423.5 million litres of milk being produced annually. Thus, the dairy industry is of great economic importance to Uruguay. Mastitis is an inflammatory reaction of the mammary gland, which has significant health and economic implications. It is the major health problem among dairy cows in Uruguay. Sub-clinical mastitis is a condition in which there is no detectable inflammatory change in the udder and no observable abnormalities in the milk. However, it reduces milk production and adversely affects milk quality. It can also be seen as a reservoir for bacteria that can later cause clinical mastitis, which has an even greater effect on health and economy. It has been shown that sub-clinical mastitis is responsible for 70% of the losses in milk production in Uruguay.